"My First Humanoid Robot" An Experience worth Sharing with Freshmen and Sophomore - Adhikari, Biikram (Journal of the Institute of Engineering, 2011)
As the world around is becoming overwhelmed with sophisticated embedded gadgets and robots, it is indispensable to create enthusiasm among students about embedded systems and robotics in their early career. While embedded platforms are an attractive option to learn and implement new technologies, most freshmen and sophomore engineering students have not acquired sufficient skills to understand and use the complex development tools needed to program these platforms. Students need simpler and spontaneous environment to experiment with their creativity and apply basic engineering concepts. Sharing an experience of building a humanoid robot with LEGO Mindstorms NXT ®, this paper presents the LEGO Mindstorms Kit as a useful tool for freshman and sophomore students to learn robotics and embedded systems. Key Words: LEGO Mindstorms; Robotics; Embedded Systems DOI: http://dx.doi.org/10.3126/jie.v8i1-2.5097 Journal of the Institute of Engineering Vol. 8, No. 1&2, 2010/2011 Page: 64-70 Uploaded Date: 19 July, 2011